Design of a Food Detection System for Environmental Care Education: Perancangan Sistem Deteksi Makanan untuk Pendidikan Peduli Lingkungan - Betri, Tigus Juni; Ibrahim, Ramdan (Journal of Vocational Education and Information Technology (JVEIT), 2024)
The food waste phenomenon in Indonesia now reaches 300 kg of food waste per person every year. This shows the urgency of environmental awareness in our society. Technology is increasingly developing but is not balanced with maximum use to preserve the earth. One of the latest technological trends, namely Artificial Intelligence, is an option that can be developed to educate the public about waste awareness. This research aims to create a design using the concept of Artificial Intelligence, namely pattern recognition for food detection to anticipate too much food waste in the food industry, namely restaurants. The design was carried out using the waterfall method which allows the design process to run coherently and precisely. Based on literature studies and expert analysis, the results of this research show that design in the form of system design and database design can be used as a basis for developing food detection applications